The Natural Wood Regime in Rivers. (27th March 2019) - Wohl, Ellen; Kramer, Natalie; Ruiz-Villanueva, Virginia; Scott, Daniel N; Comiti, Francesco; Gurnell, Angela M; Piegay, Herve; Lininger, Katherine B; Jaeger, Kristin L; Walters, David M; Fausch, Kurt D
Abstract: The natural wood regime forms the third leg of a tripod of physical processes that supports river science and management, along with the natural flow and sediment regimes. The wood regime consists of wood recruitment, transport, and storage in river corridors. Each of these components can be characterized in terms of magnitude, frequency, rate, timing, duration, and mode. We distinguish the natural wood regime, which occurs where human activities do not significantly alter the wood regime, and a target wood regime, in which management emphasizes wood recruitment, transport, and storage that balance desired geomorphic and ecological characteristics with mitigation of wood-related hazards. Wood regimes vary across space and through time but can be inferred and quantified via direct measurements, reference sites, historical information, and numerical modeling. Classifying wood regimes with respect to wood process domains and quantifying the wood budget are valuable tools for assessing and managing rivers.